Pengaruh Infrastruktur Terhadap Pertumbuhan Ekonomi di Provinsi Sulawesi Utara - Demak, Utari Dwi Larasati Kiay; Laoh , Olly Esry Harryani; Rengkung, Leonardus Ricky (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study is to analyze infrastructure in this case road infrastructure, electricity infrastructure and clean water infrastructure on economic growth in Minahasa Regency, North Minahasa, Bolaang Mongondow, Sangihe Islands and Manado City. The research was conducted from November 2022 to April 2023 in North Sulawesi Province in four districts (Minahasa, North Minahasa, Bolaang Mongondow, and Sangihe) and one city (Manado). This study uses secondary data taken from the North Sulawesi Central Bureau of Statistics and the public works department using multiple linear regression analysis methods. The results of this analysis explain that firstly road infrastructure has an impact on economic growth in Minahasa Regency, North Minahasa, Bolaang Mongondow, Sangihe Islands Regency and Manado City. The analysis explains how the impact of electricity infrastructure on economic growth in Minahasa Regency, North Minahasa, Bolaang Mongondow, Sangihe Islands Regency and Manado City, and the analysis explains how the impact of clean water infrastructure providers on economic growth in Minahasa Regency, North Minahasa, Bolaang Mongondow, Sangihe Islands Regency and Manado City.